ZOOGEOGRAPHICAL REGIONALIZATION OF THE SERBIA ACCORDING TO THE AFFINITY OF LOCAL FAUNAS OF THE SKIPPERS AND BUTTERFLIES (LEPIDOPTERA: HESPERIOIDEA & PAPILIONOIDEA) - Jakšić, Predrag (Bulletin of Natural Sciences Research, 2016)
Integrated list of skippers and butterflies of Serbia is shown. We also conducted faunal analyses of established species. Based on previous research, some regions have been identified as center of certain faunal groups. Degree of similarity of selected areas is established by Jaccard index method.  By Cluster analyses has identified links between isolated areas. Specific faunal elements of certain areas have been separated – they are diferencial species. Summerazing the obtain results, zoogeographical map of the skippers and butterflies of Serbia is done.
Keywords: Serbia; zogeography; faunal elements; butterflies